SUMO-targeted Ubiquitin Ligases as crucial mediators of protein homeostasis in Candida glabrata. - Dipika Gupta; Renu Shukla; Krishnaveni Mishra (PLoS Pathogens)
Candida glabrata is an opportunistic human pathogen, capable of causing severe systemic infections that are often resistant to standard antifungal treatments. To understand the importance of protein SUMOylation in the physiology and pathogenesis of C. glabrata, we earlier identified the components of SUMOylation pathway and demonstrated that the deSUMOylase CgUlp2 is essential for pathogenesis. In this work we show that the CgUlp2 is essential to maintain protein homeostasis via the SUMO-targeted ubiquitin ligase pathway. The dual loss of deSUMOylase and specific ubiquitin ligase, CgSlx8, results in heightened protein degradation, rendering the cells vulnerable to various stressors. This degradation affects crucial processes such as purine biosynthesis and compromises mitochondrial function in the mutants. Importantly, the absence of these ubiquitin ligases impedes the proliferation of C. glabrata in macrophages. These findings underscore the significance of SUMOylation and SUMO-mediated protein homeostasis as pivotal regulators of C. glabrata physiology and capacity to survive in host cells. Understanding these mechanisms could pave the way for the development of effective antifungal treatments.